CRIMINALIZATION POLICY OF DEEPFAKE IN INDONESIAN ELECTIONS: KEBIJAKAN KRIMINALISASI DEEPFAKE DALAM PEMILU INDONESIA - Rachmat Irvan; Junet Hariyo Setiawan (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
Technological engineering in the form of artificial intelligence (AI), particularly through deepfake content, has given rise to new forms of cybercrime that are complex and multidimensional. However, Indonesia’s positive law has yet to specifically regulate this phenomenon, resulting in legal uncertainty. This study aims to examine the effectiveness of existing regulations and to formulate an ideal criminalization policy. It employs normative juridical research with statutory and conceptual approaches. The main findings reveal that regulations such as the Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP) are reactive in nature and do not provide a technical definition of deepfake. This absence complicates digital forensic evidence and law enforcement, further exacerbated by structural weaknesses such as poor inter-agency coordination and low levels of digital literacy among the public. The scientific contribution of this article lies in its proposal for a multidimensional regulatory strategy that not only focuses on legal reform through the formulation of new criminal provisions, but also integrates the strengthening of forensic technology and the enhancement of digital literacy as preventive instruments within criminal law policy.